동통을 동반한 족관절의 만성 외측 불안정성에 있어서 마취하 스트레스 방사선 검사 - 최준영; 안희찬; 신명진; 서진수; Choi, Jun Young; Ahn, Hee Chan; Shin, Myung Jin; Suh, Jin Soo (대한족부족관절학회지, 2017)
Purpose: Anterior drawer and varus stress radiographs are commonly to diagnose chronic lateral ankle instability. We compared the preoperative stress radiographs with the intraoperative radiographs under anesthesia to determine the accuracy and efficacy of stress radiographs in an outpatient clinical environment. Materials and Methods: Data was collected from patients who underwent a modified $Brostr{\ddot{o}}m$ operation for painful chronic unilateral lateral ankle instability between January 2014 and June 2016. Subjects were divided into three groups-complete tear, partial tear, and instability without rupture-according to the status of preoperative MRI findings of the anterior talofibular ligament. The anterior drawer and varus stress radiographs were taken preoperatively and intraoperatively under anesthesia. Results: Ninety-six patients, with a mean age of 29.63 years, were enrolled. There were 39, 46, and 11 patients in the complete tear, partial tear, and instability without rupture groups, respectively. On the anterior drawer and varus stress radiographs of the affected limb, talar anterior translation and varus tilting were significantly increased by 2.56 mm and $2.0^{°}$. The gaps between the unaffected limbs were also increased by 2.47 mm and $1.32^{°}$ after anesthesia. Although the stress radiographs were taken under anesthesia, the results were often smaller than the diagnostic value. Conclusion: Stress radiographs for painful chronic lateral ankle instability taken at the outpatient clinic might be inaccurate for diagnosis.